Model Sistem Inventory Menggunakan Aplikasi Odoo - Heri Purwanto; Teguh Wiharko; Rudy Sofian; Fahmi Reza Ferdiansyah; Fernanda Rahmaeni Nur Taufik (STMIK Banjarbaru, 2023)
The application of the Inventory System in goods and services companies must be considered so that the implementation of the system work is measurable and directed. In order to quickly record and process the procurement of goods in the warehouse, Information Technology support is deemed necessary to help the system run. At PT. Nushada, the current implementation of the procurement of goods does not use a computerized system. This can hinder the company's good performance, such as printing data on the same item multiple times. The aim of this research is to assist the management of procurement of goods in companies with a computerized system assisted by the Odoo platform application. The method used in making the inventory application is the prototype development method. The result of this implementation is the formation of a goods procurement inventory application with the Odoo platform to facilitate work on the warehouse section. In further development, this application can be added a payment transaction feature.Keywords: Application Software; Inventory System; Odoo, Prototypes AbstrakPenerapan Sistem Inventory pada perusahaan barang maupun jasa harus diperhatikan agar implementasi kerja sistem terukur dan terarah. Agar cepat dalam mencatat maupun memproses pengadaan barang di gudang, dukungan Teknologi Informasi dipandang perlu untuk membantu jalannya sistem. Pada PT. Nushada, pengimplementasian pengadaan barang yang berjalan saat ini belum menggunakan sistem terkomputerisasi. Hal tersebut dapat menghambat kinerja baik perusahaan, seperti mencetak data barang yang sama secara ganda. Tujuan penelitian adalah untuk membantu pengelolaan pengadaan barang pada perusahaan dengan sistem terkomputerisasi yang dibantu dengan aplikasi platfrorm Odoo. Metode yang digunakan dalam pembuatan aplikasi inventory adalah metode pengembangannya prototype. Hasil dari pengimplementasian ini yaitu terbentuknya aplikasi inventory pengadaan barang dengan platfrorm Odoo untuk memudahkan pekerjaan pada bagian gudang. Pada pengembangan selanjutnya, aplikasi ini dapat ditambahkan fitur transaksi pembayaran.